Numerical Simulation of Cracks in Automotive Coatings Under Mechanical and Thermal Loading Using Element Free Galerkin Method. (31st October 2022) - Chilakala, Mahendra; Samyal, Rahul; Garg, Sahil; Saxena, Kuldeep K.; Gupta, Nakul
ABSTRACT: The work presented in this paper aims to delve into the applications of Element Free Galerkin Method (EFGM) which is a type of Meshless Method (MM) to the area of Automobile Engineering. EFGM is implemented to detect a change in the material property at the interface of the coating along with the identification of crack. Simulation of centre crack in coatings has been reported for the first time using EFGM. Simulations with change in crack inclination angle, change in crack length are reported. Multiple cracks are reported in the form of collinear cracks, coplanar cracks and the effect of their presence on primary crack has been discussed. This work involves the study which leads to understanding the effect of temperature on the stress fields of the cracks present in coatings. Variations of the temperature field parallel to crack and perpendicular crack shows enticing results. The effect of variation in materials properties of coating and substrate is discussed. The work reveals the nature of crack severity in automobile coatings. Various conditions depicted in this work enhance the understanding of researches in comprehending the effect of thermal load in coated materials.